Physical Education Teachers Viewed from an Economic Perspective: Review Literature Analysis Study - Indrayogi, Indrayogi; Primayanti, Intan; Soemardiawan, Soemardiawan; Syobri, Nazalus; Wahyudi, Johan (Indonesian Journal of Sport Management, 2024)
This study aims to examine the role of physical education (PE) teachers from an economic perspective through an analysis of literature reviews. In the context of education, PE teachers have an important contribution in shaping students' physical and mental health. However, from an economic perspective, their role is often underappreciated. This study analyzes various related literatures to understand how the role of PE teachers is influenced by economic factors such as salary, education budget, government policies, and socio-economic conditions of the community. The results of the study indicate that financial support and economic rewards for PE teachers have a positive correlation with the quality of education they provide. This study also reveals the need for fairer and more sustainable policies to improve the welfare of PE teachers, so that they can be more effective in carrying out their duties.